Matrix-M adjuvant triggers inflammasome activation and enables antigen cross-presentation through induction of lysosomal membrane permeabilization - Behdad Zarnegar; Berit Carow; Jens Eriksson; Eva Spennare; Pontus Öhlund; Eray Akpinar; Emelie Bringeland; Ingrid Lekberg Osterman; Lena Lundqvist; Johanna Antti; Niklas Handin; Per-Henrik Helgesson; et al. (npj Vaccines)
Abstract Matrix-M® adjuvant, containing saponins, delivers a potent adjuvant effect and good safety profile. Given that Matrix-M is composed of Matrix-A and Matrix-C particles, comprising different saponin fractions, understanding their distinct roles can provide deeper insight into the mechanism of action of Matrix-M and guide future applications. Here, we demonstrate that the antigen and Matrix-M, Matrix-A, or Matrix-C colocalize in lysosomes following uptake by bone marrow–derived dendritic cells. Matrix-M, Matrix-A, and Matrix-C induce lysosomal membrane permeabilization (LMP), but Matrix-C shows the highest LMP potential. LMP is required for interleukin (IL)-1β and IL-18 secretion in vitro. In vivo, a robust adjuvant effect of Matrix-M, Matrix-A, and Matrix-C is observed, both in the presence and absence of the NLRP3 inflammasome. LMP induced by Matrix-M, as well as Matrix-A and Matrix-C, also enables antigen cross-presentation. Thus, Matrix-induced LMP explains the capability of Matrix-M–adjuvanted protein vaccines to induce CD8+ T-cell responses.